2008
DOI: 10.1103/physrevd.78.054001
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the equation of state of QCD at finite chemical and zero temperature

Abstract: In this paper, we give a direct method for calculating the partition function, and hence the equation of state (EOS) of Quantum Chromodynamics (QCD) at finite chemical potential and zero temperature. In the EOS derived in this paper the pressure density is the sum of two terms: the first term P(µ)| µ=0 (the pressure density at µ = 0) is a µ-independent constant; the second term, which is totally determined by G R [µ](p) (the renormalized dressed quark propagator at finite µ), contains all the nontrivial µ-depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…The model-independent equations of state of strong interaction matter at finite µ and zero T are [36,37]:…”
Section: A the Equation Of Statementioning
confidence: 99%
“…The model-independent equations of state of strong interaction matter at finite µ and zero T are [36,37]:…”
Section: A the Equation Of Statementioning
confidence: 99%
“…From the first principle of QCD theory at zero temperature and finite chemical potential, the quark-number density is determined by the dressed quark propagator at finite chemical potential only [22],…”
Section: Nonlinear Susceptibilities In the Dses Frameworkmentioning
confidence: 99%
“…The baryon-number fluctuations, especially the variance, the skewness, and the kurtosis, are experimental observables (in this paper, the experimental data come from the STAR experiment at RHIC [21]). When studying the quark numbers at finite chemical potential by the fundamental theories of QCD, it is found that the quark-number density is determined by the corresponding dressed quark propagator only [22]. Then by generalizing this conclusion to the most universal situation of finite temperature and chemical potential [23], we can calculate the nth order susceptibilities at finite temperature and chemical potential, and compare them with the experimental data from RHIC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the method proposed in [24], the EOS of QCD at zero temperature and finite quark chemical potential is calculated under the hard-dense-loop (HDL) approximation [25]. A comparison between the EOS under HDL approximation and the cold, perturbative EOS of QCD proposed in [26,27] is made.…”
Section: The Equation Of State and Thermodynamics Of Nuclear Mattermentioning
confidence: 99%